2022
DOI: 10.1515/zfw-2021-0030
|View full text |Cite
|
Sign up to set email alerts
|

Der Zusammenhang zwischen sozialen Ungleichheiten und Covid-19 Fallzahlen auf Stadtteilebene – Eine Fallstudie für 46 Stadtteile der Stadt Duisburg

Abstract: Zusammenfassung Während der laufenden SARS-CoV-2-Pandemie hat die Forschung gezeigt, dass sozio-ökonomische Ungleichheiten eine entscheidende Rolle beim Verständnis der Ausbreitung des Virus spielen. Menschen mit einem niedrigeren sozio-ökonomischen Status haben eine höhere Wahrscheinlichkeit, sich mit COVID-19 zu infizieren und an dem Virus zu sterben. Da sozio-ökonomische Ungleichheiten eine starke räumliche Dimension haben, z. B. aufgrund zunehmender Ungleichheiten innerhalb von Städten, könn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…residential and commercial areas, NDVI and housing space, and the cumulative number of SARS-CoV-2 infections at the neighbourhood level in a metropolitan area in Germany. It thereby complements existing studies on the determinants of COVID-19 cases in Germany [28,29] that did not examine the role of the built environment and offers in addition a more in-depth perspective by using a high spatial resolution.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…residential and commercial areas, NDVI and housing space, and the cumulative number of SARS-CoV-2 infections at the neighbourhood level in a metropolitan area in Germany. It thereby complements existing studies on the determinants of COVID-19 cases in Germany [28,29] that did not examine the role of the built environment and offers in addition a more in-depth perspective by using a high spatial resolution.…”
Section: Discussionmentioning
confidence: 74%
“…Straßburger and Mewes (2022) examined the relationship between district socio-economic status score and SARS-CoV-2 infections at the city-district level in Duisburg, a city only a few kilometres west of Essen. Their results suggest that socially disadvantaged districts were particularly affected in the second wave of infection [ 29 ]. This is in line with our results, as two of the score components, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies indicated that socioeconomically disadvantaged areas were more susceptible to the spread of COVID-19 on a small scale. COVID-19 cases were, for example, negatively related to income (25, 26, 77) or indices based on socioeconomic data (78)(79)(80)(81)(82) and positively related to population density, average household size (77, 83,84), and the proportion of young people in the population (26,77). These analyses are still pending for Neukölln and no general statements can be made on the basis of our initial exploration.…”
Section: Spatiotemporal Patterns and Clustersmentioning
confidence: 99%
“…Socioeconomic, ethnic and geographical inequalities in COVID-19 infections and mortality have been found in many countries worldwide (1)(2)(3)(4)(5)(6)(7). For example, in the UK mortality rates in deprived areas were more than twice as high as in affluent areas (8, 9).…”
Section: Introductionmentioning
confidence: 99%